2019
DOI: 10.1002/cam4.2495
|View full text |Cite
|
Sign up to set email alerts
|

Patients' prognosis of intrahepatic cholangiocarcinoma and combined hepatocellular‐cholangiocarcinoma after resection

Abstract: Combined hepatocellular‐cholangiocarcinoma (cHCC‐CC) and intrahepatic cholangiocarcinoma (ICC) are classified into one category, but comparison of prognosis of the two carcinomas remains controversial. The aim of the current study was to investigate surgical outcomes for patients with ICC or cHCC‐CC who underwent resection in order to elucidate whether the classification of ICC and cHCC‐CC is justified. Subjects were 61 patients with ICC and 29 patients with cHCC‐CC who underwent liver resection from 2001 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Some researchers suggested that cHCC-CCA had poorer survival outcome than both HCC and CC [5], whereas other investigations showed a better or similar prognosis of cHCC-CCA compared to CC [6,7]. Several prognostic factors for cHCC-CCA have been identified, including performance status, Child-Pugh (CP) grade, tumor size, tumor number, carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) [7][8][9][10]. However, these findings still remain controversial and need further validations, due to the small sample size and inconsistent pathological diagnostic criteria.…”
Section: Ivyspringmentioning
confidence: 99%
“…Some researchers suggested that cHCC-CCA had poorer survival outcome than both HCC and CC [5], whereas other investigations showed a better or similar prognosis of cHCC-CCA compared to CC [6,7]. Several prognostic factors for cHCC-CCA have been identified, including performance status, Child-Pugh (CP) grade, tumor size, tumor number, carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) [7][8][9][10]. However, these findings still remain controversial and need further validations, due to the small sample size and inconsistent pathological diagnostic criteria.…”
Section: Ivyspringmentioning
confidence: 99%
“…The treatment options for cHCC-ICC are similar to those for HCC and ICC and include surgery, radiation, yttrium-90 radioembolization, chemotherapy, combined radiation and chemotherapy, combined surgery and chemotherapy, and triple therapy (surgery, radiation, and chemotherapy). 41 , 66 , 67 , 68 , 69 A recently retrospective analysis from 2001 to 2015 of 623 PLC patients, including 47 cHCC-ICC, 468 HCC, and 108 ICC patients, who underwent resection found that although cHCC-ICC is more poorly differentiated than HCC and ICC, it had a similar 5-year survival rate (49.7%, 54.8%, and 68.7%, respectively) and 3-year recurrence rate (57.9%, 61.5%, 56%, respectively). 70 …”
Section: Main Textmentioning
confidence: 99%
“…All patients were followed for postoperative recurrence as described previously (26). Briefly, tumor marker levels, including those of carcinoembryonic antigen and carbohydrate antigen 19-9 (CA19-9), were measured, and imaging studies, including computed tomography and ultrasonography, were performed every three months in all patients.…”
Section: Follow-up After Operationmentioning
confidence: 99%